Transcription elongation factor AFF2/FMR2 regulates expression of expanded GGGGCC repeat-containing C9ORF72 allele in ALS/FTD - Yeliz Yuva-Aydemir (Nature Portfolio, 2019)
Mechanisms of transcription of expanded G4C2 repeats in C9ORF72, associated with ALS/FTD, are not fully understood. Here authors use both Drosophila and C9ORF72 iPSC-derived neurons and identify AFF2/FMR2 as a regulator of poly(GR) toxicity by regulating expression of the expanded G4C2 repeats.